If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-12=6/5x
We move all terms to the left:
-12-(6/5x)=0
Domain of the equation: 5x)!=0We add all the numbers together, and all the variables
x!=0/1
x!=0
x∈R
-(+6/5x)-12=0
We get rid of parentheses
-6/5x-12=0
We multiply all the terms by the denominator
-12*5x-6=0
Wy multiply elements
-60x-6=0
We move all terms containing x to the left, all other terms to the right
-60x=6
x=6/-60
x=-1/10
| 3p^2+p+8=0 | | 8b=9+5b | | 5y^2-6y+6=0 | | 13d−3d=20 | | 7x+9=7x | | 9/5a(a-5)=40 | | -3u=-2u-8 | | 5+r=22 | | 4y+3(-3y)=10 | | x+15)/2=13 | | -3-8(n+40)=-91 | | 5q=4q+4 | | 7(2y-8)=24 | | -3-8(n+40=-91 | | 6–3x=15+4x | | 3v^2+5v+1=0 | | 44=2x-6x | | 6r=8r+10 | | 4t^2-9t+8=0 | | 164=4(-7n-8) | | 3(3x+1)=7x | | -7j+4j=3j | | -85=6-7(x+5) | | 3x-9=7x-5+x | | 6(x-2)=5-4(x-1) | | 9(x+2)^2-3=-152 | | 4=7u=60 | | 2x+4x+18+6x+13=180 | | 8+4(7x-8)=-14 | | 514=x−25 | | 4(4x-2)=1 | | -4(v+9)=-12 |